Effects of essential oil compounds on survival of Listeria monocytogenes and Escherichia coli O157:H7 in çiğ köfte - Dikici, Abdullah; İlhak, O. İrfan; Çalıcıoğlu, Mehmet (My University, 2013)
This study was undertaken to evaluate the effects of some essential oil compounds for the inactivation of Listeria monocytogenes and Escherichia coli O157:H7 in çiğ köfte. In experiment 1, a çiğ köfte batch was inoculated with high levels of E. coli O157:H7 or L. monocytogenes (7.00 log10 cfu/g) and the batches were divided into 6 groups. Each group was treated with 18 mL/kg of normal saline, cineole, limonene, carvone, linalool, or eugenol. Treatment with carvone, linalool, and eugenol resulted in a significant (P < 0.05) decrease in the numbers of both pathogens. In experiment 2, the çiğ köfte was inoculated with the same pathogens and each group was treated with 0 (control), 20, 22.5, and 25 mL/kg of eugenol. Increases in concentration did not cause a difference in pathogen reduction. The results showed that eugenol, carvone, and linalool can be used for the inactivation of E. coli O157:H7 and L. monocytogenes in çiğ köfte or similar foods.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Essential oil compounds; ground beef; antimicrobial; nonthermal inactivation